Pandemia e exclusão social: rupturas sociais e projetos de vida de adolescentes brasileiros em cumprimento de medida socioeducativa de internação - Sena, Bárbara Cristina Soares (2023)
The COVID-19 pandemic has heightened concerns about the conditions of socially vulnerable adolescents in Brazil and around the world. Containment measures and the health, economic and social consequences increased the risks already experienced by this population. Therefore, the main objective of this research was to understand the impacts that the pandemic had with regard to social and relational ruptures caused by the COVID-19 pandemic in the lives of adolescents in situations of social exclusion, more specifically, adolescents fulfilling socio-educational measures of hospitalization. Furthermore, the aim was also to verify the influences and changes of the pandemic context on their life projects and future expectations. Based on the assumptions of the Bioecological Theory of Human Development, we sought to develop analyzes that made it possible to articulate the impact of the pandemic in the contexts of adolescents who were already experiencing situations of social exclusion and its consequences in the face of possible ruptures with significant people and spaces, as well as in your life projects. This was a qualitative, exploratory, descriptive study with a cross-sectional design. Twenty-two adolescents living in the five macro-regions of Brazil participated in the investigation, aged between 16 and 19 years old, male and undergoing a socio-educational hospitalization measure. For data collection, the following instruments were used: i) Questionnaire on the sociodemographic characterization of participants; ii) Life Project Questionnaire; and iii) Semi-structured Interview. The Thematic Analysis (TA) technique was used to analyze the data. The results indicate that the Covid-19 pandemic considerably impacted the social and relational bonds of adolescents who were hospitalized. There was an increase, specifically, of ruptures with school spaces, as difficulties already existed before the pandemic and these were aggravated by the way educational spaces were organized. But, at the same time, there was also a strengthening of these adolescents' family relationships, mainly due to the increased interaction made possible by the period of social isolation. Regarding life projects, the research revealed a positive perception among adolescents in identifying the presence of goals and expectations for the future. However, the context of the pandemic added even more difficulties to the reality of adolescents who were already experiencing situations of social exclusion, such as the absence of work and worsening socioeconomic difficulties. The thesis questions, in such a way, the uncritical and hegemonic look directed at the population investigated with regard to the topics covered. An individualizing conception of the factors involved in development can lead to biased analyzes and practices regarding important aspects for the present and future of these adolescents.